Research progress of endoplasmic reticulum stress of hypoxic pulmonary hypertension - LIU Xingxing, WANG Weiwei, YUAN Haoxin (Jichu yixue yu linchuang, 2023)
Hypoxic pulmonary hypertension (HPH) is a serious complication caused by long-term hypoxia,which is characterized by persistent vasoconstriction and irreversible vascular remodeling. The hypoxia may destroy protein folding process in endoplasmic reticulum and activate endoplasmic reticulum stress(ERS). As the core response of cell stress, ERS is closely related to the development of HPH.